The Urgency of Integrating Character Education in The Elementary School Curriculum - Wiladhatin Ira Kusumawati; Marno Nurullah; Samsul Susilawati (Yayasan Adra Karima Hubbi, 2024)
Character education is a crucial element in the development of students at the elementary school level, where they begin to form identities and moral values. This article discusses the strategy of character education for students at the elementary school level and the urgency of integrating character education in the elementary school curriculum as an effort to form a young generation who are not only cognitively intelligent, but also have good character The method of writing this article uses the literature review method. In this method, the author searches for themes related to character education in the elementary school curriculum. Then continue by summarizing the results of related literature to find the intended results. The results of this study reveal that in the elementary school curriculum, the integration of character education can be applied through school subjects such as Civic Education (PKn) and Social Sciences. In addition, character education can also be integrated in activities in schools to build social awareness and the student environment. Character education helps students become responsible individuals and care for others and the environment, while reducing bullying behavior. Through routine activities and example, students are taught to have sensitivity to the environment and others. Thus, character education plays an important role in creating a generation that is ethical and able to face moral challenges in daily life.